Influencing policy to reduce child marriage in India: Reflections from Young Lives - Singh, DR; Ford, K (Young Lives, 2020)
In this latest Young Lives Insights Report, Dr Renu Singh, Young Lives India Country Director, discusses why she continues to work so passionately on addressing child marriage, how longitudinal research can influence policy change and what the potential impact of the current COVID-19 pandemic might be on levels of child marriage. Renu is in conversation with Kath Ford, who is the former Young Lives Programme Manager and now an International Development Policy Advisor.